Solar Radiation-Associated Adaptive SNP Genetic Differentiation in Wild Emmer Wheat, Triticum dicoccoides - Ren, Jing; Chen, Liang; Jin, Xiaoli; Zhang, Miaomiao; You, Frank M.; Wang, Jirui; Frenkel, Vladimir; Yin, Xuegui; Nevo, Eviatar; Sun, Dongfa; Luo, Ming-Cheng; Peng, Junhua (Frontiers in Plant Science, 2017)
Whole-genome scans with large number of genetic markers provide the opportunity to investigate local adaptation in natural populations and identify candidate genes under positive selection. In the present study, adaptation genetic differentiation associated with solar radiation was investigated using 695 polymorphic SNP markers in wild emmer wheat originated in a micro-site at Yehudiyya, Israel. The test involved two solar radiation niches: (1) sun, in-between trees; and (2) shade, under tree canopy, separated apart by a distance of 2–4 m. Analysis of molecular variance showed a small (0.53%) but significant portion of overall variation between the sun and shade micro-niches, indicating a non-ignorable genetic differentiation between sun and shade habitats. Fifty SNP markers showed a medium (0.05 ≤ FST ≤ 0.15) or high genetic differentiation (FST > 0.15). A total of 21 outlier loci under positive selection were identified by using four different FST-outlier testing algorithms. The markers and genome locations under positive selection are consistent with the known patterns of selection. These results suggested that genetic differentiation between sun and shade habitats is substantial, radiation-associated, and therefore ecologically determined. Hence, the results of this study reflected effects of natural selection through solar radiation on EST-related SNP genetic diversity, resulting presumably in different adaptive complexes at a micro-scale divergence. The present work highlights the evolutionary theory and application significance of solar radiation-driven natural selection in wheat improvement.